Kreativitas Menulis dan Dampak Peningkatan Diri: Pengabdian - Imelda Oliva Wissang; Maria Marieta Bali Larasati; Maria Floriana Serlin; Alfonsa Suku (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This service aims to describe the impact of writing on self-development together with 17 accompanying teachers and participants of the FLS3N and HARDIKNAS competitions held by MKKS (Principal Working Conference) with the Short Story Writing competition for SMA level throughout Ngada Regency on May 6, 2025 at SMAK Regina Pacis Bajawa. The activity method uses a participant active learning approach. The activities designed are very helpful for participants to participate actively and creatively in participating in activities. Through writing activities, it can have a positive impact on self-improvement. The positive impact of writing short stories on self-improvement, both mentally, spiritually, socially and in terms of abilities, cognitive, competence and professionalism, can be explained as follows, (1) has an impact on the habit of building a spirit of discipline, (2) has an impact on mental balance, (3) has an impact on critical and productive thinking, and (4) has an impact on awareness of identity and moral and social responsibility.